Improving Nutrition and Health through Non-timber Forest Products in Ghana (Journal of Health, Population and Nutrition, 2011)
Nutrition and health are fundamental pillars of human development across the entire life-span. The potential role of non-timber forest products (NTFPs) in improving nutrition and health and reduction of poverty has been recognized in recent years. NTFPs continue to be an important source of household food security, nutrition, and health. Despite their significant contribution to food security, nutrition, and sustainable livelihoods, these tend to be overlooked by policy-makers. NTFPs have not been accorded adequate attention in development planning and in nutrition-improvement programmes in Ghana. Using exploratory and participatory research methods, this study identified the potentials of NTFPs in improving nutrition and food security in the country. Data collected from the survey were analyzed using the SPSS software (version 16.0). Pearson’s correlation (p